Tongan women and leadership in New Zealand : a thesis presented in partial fulfilment of the requirements of the degree of Master in Business Studies at Massey University - Paea, Seluvaia Talikivaha (Massey University, 2016)
This study aims to explore how Tongan women practice leadership in New Zealand organizations. To understand the Tongan women’s leadership practice involves understanding the factors that underpin the philosophy behind their practice of leadership in their given contexts. The development of this exploration study was completed using a qualitative research framework with a focus on interpretative study interlaced with the Kakala model to produce a feminist interpretive qualitative study. I employed the talanoa method in my data collection to assist the research framework to gather valid and indepth reflections by the participants. I used the thematic analysis to analyse the data. The findings indicated how Tongan women in New Zealand organizations practice leadership based on frames that they observed and experienced during their upbringing and life journey. Numerous factors or strands emerged from the findings that weave together to produce the participants’ understanding and sensemaking of leadership. During the participants’ practice of leadership in their given contexts, they reframed some of the pre-concieved frames that enhance their leadership understanding and leadership practices. I used the metaphorical process of lalanga fala to frame the participants’ ontological narratives on their sensemaking and practice of leadership. This study highlights the value of understanding the frames that shaped the understanding of Tongan women in New Zealand on leadership. How they practice leadership in their given contexts relates to the frames that they see through. The use of framing helped to motivate participants to contribute in leadership acts no matter what position they hold in an organization.
Keywords: Leadership in women; Tongans; New Zealand